2009
DOI: 10.1097/sle.0b013e3181a620dc
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Abdominal Wall Bleeding Complications at Trocar Sites

Abstract: Abdominal wall bleeding may complicate any laparoscopic procedure. Piercing or laceration of vessels transversing the abdominal wall during trocar placement is generally the cause. Bleeding may occur at the very beginning of the surgery but, in some cases, it may go unrecognized for a while complicating the operation and the postoperative course. Planned and careful trocar placement can prevent most of these instances that otherwise can be readily managed avoiding severe morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Although trocar-related injury is uncommon, it is enough of a problem that various methods of prevention and treatment are still being investigated 10, 11. When ancillary ports are inserted, it increases the risk of injury to the inferior epigastric vessels 12.…”
Section: Discussionmentioning
confidence: 99%
“…Although trocar-related injury is uncommon, it is enough of a problem that various methods of prevention and treatment are still being investigated 10, 11. When ancillary ports are inserted, it increases the risk of injury to the inferior epigastric vessels 12.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular anatomy of the abdominal wall was studied in many human cadavers but with wide variation in results [13]. A zone of approximately 4-8 cm away from the midline is named the dangerous zone for abdominal wall vascular injuries [12, 13] but Saber et al .…”
Section: Discussionmentioning
confidence: 99%
“…A zone of approximately 4-8 cm away from the midline is named the dangerous zone for abdominal wall vascular injuries [12, 13] but Saber et al . [14] in a study on abdominal and pelvic CT images of 100 patients found that “The average distance of the epigastric vessels from the midline for both left and right sides is consistently higher for older patients and those with body mass index more than or equal to 26.3 in all sections”.…”
Section: Discussionmentioning
confidence: 99%
“…In morbid obese patients undergoing bariatric surgery, control of the bleeding requires enlargement of the incision and placement of deep sutures, which is technically complicated because of the deep location of the haemorrhage source; at the ends, it leads to larger wounds, associated with more postoperative pain, an increased risk of wound infections and ugly scars. When the bleeding is not completely stopped, it can lead to haematoma formation and even massive haemoperitoneum [1][2][3].…”
Section: Introductionmentioning
confidence: 99%